Of inflammasomes and pathogens – sensing of microbes by the inflammasome - Franz Bauernfeind; Veit Hornung (EMBO Molecular Medicine, 2013)
Abstract Inflammasomes are signalling platforms that sense a diverse range of microbial products and also a number of stress and damage associated endogenous signals. Inflammasome complexes can be formed by members of the Nod‐like receptor family or the PYHIN family member AIM2. Upon formation, inflammasomes trigger proteolysis of caspase‐1, which subsequently leads to a potent inflammatory response through the maturation and secretion of IL‐1 family cytokines, which can be accompanied by an inflammatory cell death termed pyroptosis. Here, we review the sensing mechanisms of the currently characterized inflammasome complexes and discuss how they are involved in the innate immune response against microbial pathogens. We especially highlight recent advances in the molecular understanding of how microbial patterns are detected and discriminated from endogenous compounds by inflammasome sensors. Further, we review how inflammasomes contribute to the anti microbial host defense by cytokine‐dependent and cell autonomous mechanisms. This review is part of the review series on host‐pathogen interactions. See more reviews from this series. .